Analisis Faktor-Faktor yang Mempengaruhi Hasil Tangkapan Rawai Dasar yang Beroperasi di Perairan Teluk Bone Kabupaten Kolaka - Ilma Lana; Muslim Tadjuddah; Syamsul Kamri; Ahmad Mustafa; Hasnia Arami (PekaBuana : Jurnal Ilmiah Teknologi dan Manajemen Perikanan Tangkap, 2022)
Kolaka Regency is one of the areas that has considerable potential in the field of fisheries which must be utilized as well as possible. One of the utilization of fisheries potential is the operation of basic longlines. Until now, it is not known what factors affect the catch of fish on longlines. Information on factors affecting longline catch is needed so that fishing operations can run optimally. The purpose of this study was to determine the variables that affect the longline catch. The variables analyzed in this study were the length of immersion, the size of the bait, the number of hooks, temperature and salinity. This research was conducted for two months, namely in November-December 2021 in Bone Bay waters, around Kolakaasi Village, Kolaka Regency. The data analysis methods used are curve estimation regression analysis and principal component analysis (PCA). Result of the research are  factors that affect bottom longline catch are temperature and salinity. The results of PCA analysis also show that there is a strong relationship between temperature and salinity factors on the amount of bottom longline catches in the waters around Kolakaasi Village seen from the contribution value of these two factors, namely temperature and salinity  is included in the strong category. This relationship shows that the temperature and salinity values affect the amount of bottom line catch.